A sociological exploration of the tensions related to interprofessional collaboration in acute-care discharge planning. Issue 2 (3rd March 2016) - Goldman, Joanne; Reeves, Scott; Wu, Robert; Silver, Ivan; MacMillan, Kathleen; Kitto, Simon
ABSTRACT: Patient discharge is a key concern in hospitals, particularly in acute care, given the multifaceted and challenging nature of patients' healthcare needs. Policies on discharge have identified the importance of interprofessional collaboration, yet research has described its limitations in this clinical context. This study aimed to extend our understanding of interprofessional interactions related to discharge in a general internal medicine setting by using sociological theories to illuminate the existence of, and interplay between, structural factors and microlevel practices. An ethnographic approach was employed to obtain an in-depth insight into healthcare providers' perspectives, behaviours, and interactions regarding discharge. Data collection involved observations, interviews, and document analysis. Approximately 65 hours of observations were undertaken, 23 interviews were conducted with healthcare providers, and government and hospital discharge documents were collected. Data were analysed using a directed content approach. The findings indicate the existence of a medically dominated division of healthcare labour in patient discharge with opportunities for some interprofessional negotiations; the role of organizational routines in facilitating and challenging interprofessional negotiations in patient discharge; and tensions in organizational priorities that impact an interprofessional approach to discharge. The findings provide insight into the various levels at which interventions can be targeted to improve interprofessional collaboration in discharge while recognizing the organizational tensions that challenge an interprofessional approach.